2021
DOI: 10.3389/fsufs.2021.603892
|View full text |Cite
|
Sign up to set email alerts
|

The Realm of Microbial Pigments in the Food Color Market

Abstract: Colors are added to food items to make them more attractive and appealing. Food colorants therefore, have an impressive market due to the requirements of food industries. A variety of synthetic coloring agents approved as food additives are available and being used in different types of food prepared or manufactured worldwide. However, there is a growing concern that the use of synthetic colors may exert a negative impact on human health and environment in the long run. The natural pigments obtained from anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…have been isolated from the rind of brownish cheese in several environments, producing interesting extracellular molecules, such as enzymes [2] and biopigments [3]. Pigment production from biological non-pathogenic agents, such as those found in some food commodities, has attracted increased interests in recent years [3,4]. Nature produces many biopigments from various resources, including microorganisms, which are possible alternatives to synthetic dyes and pigments currently employed [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been isolated from the rind of brownish cheese in several environments, producing interesting extracellular molecules, such as enzymes [2] and biopigments [3]. Pigment production from biological non-pathogenic agents, such as those found in some food commodities, has attracted increased interests in recent years [3,4]. Nature produces many biopigments from various resources, including microorganisms, which are possible alternatives to synthetic dyes and pigments currently employed [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…4 272.09 (20%); 165.05 (27%); 147.04 (15%); 138.03 (11%); 123.04 (29%) 4 272.09 (20%); 165.05 (27%); 147.04 (15%); 138.03 (11%); 123.04 (29%) 4 272.09 (20%); 165.05 (27%); 147.04 (15%); 138.03 (11%); 123.04 (29%)…”
mentioning
confidence: 99%
“…The molecules capable of bestowing color, owing to their ability to absorb light in the visible range are referred as pigments. Nevertheless, by chemical definitions, pigments are insoluble colored substances while colorants are soluble colored substances ( Rana et al, 2021 ). By 2027, the market value of dyes and pigments is expected to reach 33.2–49.1 billion dollars ( Chatragadda and Dufossé, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fatal disadvantage of synthetic colorant is its toxicity to humans [3]; previous studies have found that even if the intake dose of some colorants is low, long-term intake still carries a risk of teratogenicity, carcinogenesis and genotoxicityon in the human population [4,5]. Currently, natural colorants obtained from various animals and plants are being discussed and explored for their physiological activities to alleviate harm caused by synthetic colorants [6,7].…”
Section: Introductionmentioning
confidence: 99%